2017
DOI: 10.1371/journal.pone.0187105
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptome analysis reveals genes related to cold tolerance in seabuckthorn carpenter moth, Eogystia hippophaecolus

Abstract: Seabuckthorn carpenter moth, Eogystia hippophaecolus (Lepidoptera: Cossidae), is an important pest of sea buckthorn (Hippophae rhamnoides), which is a shrub that has significant ecological and economic value in China. E. hippophaecolus is highly cold tolerant, but limited studies have been conducted to elucidate the molecular mechanisms underlying its cold resistance. Here we sequenced the E. hippophaecolus transcriptome using RNA-Seq technology and performed de novo assembly from the short paired-end reads. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 59 publications
7
27
0
Order By: Relevance
“…These were comparable to other larval Lepidoptera transcriptomes in terms of number of transcripts and N50 values (e.g. [39,40]). For a better representation of the complete larval transcriptome we combined the early and late instar sequences to assemble and annotate a reference transcriptome.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These were comparable to other larval Lepidoptera transcriptomes in terms of number of transcripts and N50 values (e.g. [39,40]). For a better representation of the complete larval transcriptome we combined the early and late instar sequences to assemble and annotate a reference transcriptome.…”
Section: Resultssupporting
confidence: 82%
“…Similar to other larval Lepidoptera, biological regulation and metabolic process (in biological process), catalytic activity and binding (in molecular function) and cell and cell part (in cellular component) were amongst the top subcategories represented (Fig 4) (e.g. [39,41] Lepidoptera are one of the largest insect orders, with >157,000 described species [42]. Many species are of economic significance as forest and agricultural pests, and ecologically significant as pollinators and food sources [43].…”
Section: Plos Onementioning
confidence: 93%
“…This analysis mapped all of the annotated genes to GO terms in the database and counted the number of genes associated with each term. The Perl script was then used to plot the GO functional classification for the UniGenes with a GO term hit to view the distribution of gene functions [ 35 ]. The obtained annotation was enriched and refined using TopGo (R package) with the “elim” method and the Kolmogorov–Smirnov test [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptome analysis revealed that low temperature response process of this plant parasite nematode is also a genetic process regulated by many genes. The past 15 years has witnessed a rapid progress in the understanding of how low temperature influenced the genetic response patterns of many plant pests with RNA sequencing method [21,22,23,24,25,26]. However, little is known about how B. xylophilus , which is also one of the most destructive pine tree pests, genetically responded to low temperature.…”
Section: Discussionmentioning
confidence: 99%